Analysis of Critical Success Factors for KM Foundation in a Consulting Company - Tanjung, Aldiyan Muhammad; Sensuse, Dana Indra (Universitas Dharma Wacana, 2024)
In the business world, Knowledge Management (KM) is increasingly recognized as a crucial factor for organizational success, especially within consulting firms. This research investigates the Critical Success Factors (CSFs) necessary for the effective implementation of KM in consulting firms. Faced with the complexities and challenges of a dynamic business environment, where efficient KM is vital for delivering high-quality services, this study conducts a thorough review of the CSFs related to KM foundations in consulting firms. The aim is to identify the CSFs essential to KM foundations. Using a Systematic Literature Review (SLR) based on the PRISMA methodology, the study synthesizes findings from five databases. From an initial pool of 1,173 papers, the selection was narrowed down to 20 papers with the most relevant content for analysis, detailing the CSFs essential to KM foundations. These factors are categorized into several dimensions, including technology, strategy, leadership, organizational culture, and regulatory policies, each contributing uniquely to the effective implementation of KM in consulting firms.